The Scientific Publishing Women, A Faculty Member At Damascus University, In The Scientific Journals Of Damascus University (Damascus University Journal of educational and Psychologyical sciences, 2023)
The study aimed to know the activity of women, a faculty member at Damascus University, in the field of scientific publishing in the scientific journals of Damascus UniversityIt was found that the proportion of research published by women in university journals to the total research published in the five years from 2015 to 2019was 26%, about one third of what was published by men. And that the highest percentage of scientific publication achieved by women is in the field of Arts and Humanities, which amounted to 41% of the total published research. The lowest percentage was in the field of economic and legal sciences, which amounted to 14% of the total published research. And the percentage of published research for women with the academic rank of "professor" is lower than for men with the academic rank of professor, reaching 11%, compared to 13% for Men, And the percentage of published research for women that was done in partnership with women amounted to 37% less than the percentage of research that was done with her male colleague in partnership with men, which amounted to 44%.The percentage of published research for women in charge of administrative work was 24%, compared to 75% for men.The study revealed a number of obstacles which weaks the women's activity in scientific publishing. some recommendation suggests to develop the efforts of women faculty members in the field of scientific publishing.
Keywords: Women faculty member; Scientific Publishing; Refereed scientific journals; Damascus University